PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR MELALUI KOMITMEN ORGANISASIONAL - Retno Wulandari; Woro Utari (Universitas Triatma Mulya, 2023)
The purpose of this study is to describe organizational citizenship behavior, organizational commitment, organizational culture and work motivation of employees at the Public Works Department (DPU) of Highways and Spatial Planning in Bojonegoro Regency. To examine and analyze the influence of organizational culture and work motivation on employee organizational citizenship behavior through organizational commitment. The population is 125 people with a sample of 125 people using total sampling. The data analysis technique uses Path Analysis SEM with Smart-PLS. Based on the results of the analysis, it can be concluded that organizational culture, work motivation, organizational commitment and organizational citizenship behavior of DPU Bina Marga and Spatial Planning in Bojonegoro Regency are in good condition. Organizational culture and work motivation have a significant effect on organizational commitment. Organizational culture and organizational commitment have a significant effect on organizational citizenship behavior. Work motivation has no significant effect on employee organizational citizenship behavior. Organizational culture and work motivation have a significant effect on employee organizational citizenship behavior.